2005
DOI: 10.1289/ehp.7240
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and Farm Exposures in a Cohort of Rural Iowa Children

Abstract: Epidemiologic studies of farm children are of international interest because farm children are less often atopic, have less allergic disease, and often have less asthma than do nonfarm children—findings consistent with the hygiene hypothesis. We studied a cohort of rural Iowa children to determine the association between farm and other environmental risk factors with four asthma outcomes: doctor-diagnosed asthma, doctor-diagnosed asthma/medication for wheeze, current wheeze, and cough with exercise. Doctor-dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
3
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(109 citation statements)
references
References 43 publications
3
102
3
1
Order By: Relevance
“…IFAP operations, for example, may introduce nitrates, microbial pathogens, veterinary pharmaceuticals, hormones, and other contaminants into groundwater and surface water-often via the application of animal waste-thus contributing to a range of adverse health and ecological effects (19). Air degradation: IFAP operations are frequently associated with elevated indoor and downwind concentrations of airborne pollutants, including ammonia, hydrogen sulfide, and airborne particulates, which contribute to respiratory illnesses and other adverse health effects among workers, their families, and nearby residents (64,101,105,138). Similarly, pesticide applications may present health risks to agricultural workers (20) and nearby residents (93,146).…”
Section: Consolidationmentioning
confidence: 99%
“…IFAP operations, for example, may introduce nitrates, microbial pathogens, veterinary pharmaceuticals, hormones, and other contaminants into groundwater and surface water-often via the application of animal waste-thus contributing to a range of adverse health and ecological effects (19). Air degradation: IFAP operations are frequently associated with elevated indoor and downwind concentrations of airborne pollutants, including ammonia, hydrogen sulfide, and airborne particulates, which contribute to respiratory illnesses and other adverse health effects among workers, their families, and nearby residents (64,101,105,138). Similarly, pesticide applications may present health risks to agricultural workers (20) and nearby residents (93,146).…”
Section: Consolidationmentioning
confidence: 99%
“…Several studies [2][3][4][5][6] have shown that growing up on a farm is associated with a lower prevalence of sensitisation and hay fever among children, a fact that backs up the hygiene hypothesis. Different studies [7][8][9][10][11] have suggested that the effect of childhood farm living on sensitisation and hay fever may persist until adulthood.…”
mentioning
confidence: 99%
“…Merchant and co-workers (2005) found that exposure to farm animals early in life was not protective against asthma. Those children living on farms that raised swine actually had significantly higher rates of diagnosed asthma and/or asthma symptoms compared with those not living on farms or those living on farms that did not raise swine (Merchant et al, 2005). These authors suggested that previous studies that considered only doctor-diagnosed asthma may have underestimated the true prevalence of asthma among farm children (Merchant et al, 2005).…”
Section: ) Indoor Airmentioning
confidence: 99%